Work from home—Work engagement amid COVID‐19 lockdown and employee happiness. Issue 4 (9th June 2021) - Mehta, Prashant
Abstract : Prolonged lockdown as a part of the community mitigation steps to control the spread of the corona virus has led to massive work reorganization throughout the world. Companies as well as individuals are attempting to adjust to this new world of work. Organizations have shifted substantial parts of their work for certain sets of jobs to a "work from home (WFH)" format. The aim of this study is to investigate the relationship between WFH) work engagement and perceived employee happiness. WFH work engagement was hypothesized to be influenced by WFH autonomy, WFH convenience, and WFH psychosocial safety. All of the constructs were adapted from established scales. Convenience sampling was used for data collection as, under the circumstances, this was the only viable method. Partial least squares structural equation modelling was used for data analysis. Results from this study indicate that WFH work engagement was able to predict a 23.9% variance in perceived happiness, while exogenous constructs, such as WFH autonomy, WFH convenience, and WFH psychosocial safety, were able to predict a 25.2% variance in WFH work engagement. Further f 2 effect size (0.313) between WFH work engagement and happiness indicates high effect size. In order to assess the predictive relevance of the model, a blindfolding procedure was used to obtain Q 2 values. Q 2 values greater than zero indicate that the model has predictive relevance.